(A-LIEP 2011):Factors That Influence the Establishment of a Network of Medical Libraries in the Philippines / Joenabie A. Encanto - A. Encanto, Joenabie (2011)
The paper sought to identify the factors affecting the establishment of a network of medical libraries in the Philippines. The paper dealt with the following questions: What facilitates or hinders the establishment of a network of medical libraries in the Philippines? What are the advantages and disadvantages of having a network? Is it feasible to establish such network? Who will manage the network? What are the network‘s functions and services? What are the requirements to join this network? What are the governing policies and guidelines? The researcher sent survey questionnaires to heads of medical libraries who are members of the Medical and Health Librarians Association of the Philippines (MAHLAP) and/or the Association of Philippine Medical Colleges (APMC). After the initial survey, the researcher conducted focus group discussions (FGD) participated by the MAHLAP 2010 Board of Officers. The researcher also interviewed networking experts and heads of medical institutions to obtain their opinion and suggestions on network establishment. Frequency analysis was used to count preferences of librarians regarding the facilitating and hindering factors affecting the establishment of a network of medical libraries. The study revealed that the key factors affecting the establishment of a network include administrative support and budget to address hindrances such as networking costs and other requirements in joining a network. Attaining these key factors would direct the readiness of medical librarians and libraries in establishing a medical library network. The researcher recommends that potential member libraries sit down and further discuss the establishment of a network of medical libraries. MAHLAP should take the initiative to convene its members and present to them draft policies and guidelines. Once discussed, this can be submitted to APMC for the heads of institutions review and approval. Once the invitation for membership is approved, librarians can meet to finalize the guidelines.